Sequence Variation of MHC Class II DQB Gene in Bottlenose Dolphin (Tursiops truncatus) from Taiwanese Waters - Wei-Cheng Yang (Taiwania, 2008)
The major histocompatibility complex (MHC) is a large multigene coding for glycoproteins that play a key role in the initiation of immune responses in vertebrates. For a better understanding of the immunologic diversity in thriving marine mammal species, the sequence variation of the exon 2 region of MHC DQB locus was analyzed in 42 bottlenose dolphins (Tursiops truncatus) collected from strandings and fishery bycatch in Taiwanese waters. The 172 bp sequences amplified showed no more than two alleles in each individual. The high proportion of non-synonymous nucleotide substitutions and the moderate amount of variation suggest positive selection pressure on this locus, arguing against a reduction in the marine environment selection pressure. The phylogenetic relationship among DQB exon 2 sequences of T. truncatus and other cetaceans did not coincide with taxonomic relationship, indicating a trans-species evolutionary pattern.